Model-based system tool for Thai Tax Revenue Forecasting (MBS-TTRF) - Jarernsri L. Mitrpanont (2018)
Model-Based System Tool for Thai Tax Revenue Forecasting (MBS-TTRF) is a model-based management system used to provide the flexibility and increase efficiency of Thai Tax Revenue Forecasting in the Revenue Department (RD). MBSTTRF contains five essential model-categories for Tax Revenue Forecasting, i.e., ETTRF Models, NITTRF Models, STTRF Models, TTRF A Models, and TTRFAC Models. The system supports the data analytical functions: Sensitivity, What-if and Goal-seeking analysis, useful for analyzing results before making a decision. Furthermore, this system also improves the accuracy of Thai Tax Revenue Forecasting by adding regression approach to NITTRF. The experimental results showed that NITTRF generated better results than the existing model-ETTRF. The results also showed that MBS-TTRF is suitable to assist a user/decision maker as an alternative model to forecast tax revenue and reduces time for Thai Tax Revenue Forecasting operation that depends mainly on human expertise. © 2011 IEEE.